Decolonizing the Curriculum: Policy Implications for Indigenous Knowledge Integration in National Education Systems - Nakashi Kawa Miuka; Jamila Tufu (International Journal of Post Axial: Futuristic Teaching and Learning, 2025)
This study explores the integration of Indigenous knowledge into national education systems as a central strategy for curriculum decolonization. Focusing on case studies from Canada and New Zealand, the research investigates how policy frameworks and classroom practices intersect to promote or hinder the inclusion of Indigenous epistemologies. Findings reveal that while national policies in both countries emphasize cultural inclusion and reconciliation, actual implementation varies widely across schools. Successful integration depends significantly on community engagement, teacher training, and leadership support. However, systemic challenges such as standardized assessments, insufficient curricular guidance, and minimal Indigenous representation in policymaking continue to limit the depth of curricular transformation. The study highlights the importance of creating dialogic and culturally grounded educational environments to foster equity, identity affirmation, and epistemic justice in multicultural societies.